2009
DOI: 10.2174/156802609789630910
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 IN Inhibitors: 2010 Update and Perspectives

Abstract: Integrase (IN) is the newest validated target against AIDS and retroviral infections. The remarkable activity of raltegravir (Isentress ® ) led to its rapid approval by the FDA in 2007 as the first IN inhibitor. Several other IN strand transfer inhibitors (STIs) are in development with the primary goal to overcome resistance due to the rapid occurrence of IN mutations in raltegravirtreated patients. Thus, many scientists and drug companies are actively pursuing clinically useful IN inhibitors. The objective of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
87
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 146 publications
1
87
0
Order By: Relevance
“…Clinically relevant IN inhibitors show selectivity for the ST reaction and only weakly inhibit 3= processing (45). These compounds are referred to as IN strand transfer inhibitors (INSTIs).…”
mentioning
confidence: 99%
“…Clinically relevant IN inhibitors show selectivity for the ST reaction and only weakly inhibit 3= processing (45). These compounds are referred to as IN strand transfer inhibitors (INSTIs).…”
mentioning
confidence: 99%
“…The U.S. Food and Drug Administration (FDA) approval of raltegravir (3) for experienced patients, and more recently for naive patients, has significantly impacted AIDS therapy (10). However, clinical resistance to RAL emerges due to mutations in IN (13,17). Biochemical characterization of recombinant mutant IN enzymes demonstrated that RAL resistance involves one of three main mutations: Y143R, G140S-Q148H, and N155H (14,16,18).…”
mentioning
confidence: 99%
“…It has been reported that halogen substitution on the aryl group showed significant potency and selectivity against IN and viral replication in cell culture 13 . Several IN inhibitors containing different halogen substitution on the aryl group had been tested in the clinic, including MK-2048, GS-9137 and MK-0518 ( Figure 1) 14,15 . Especially MK-0518, also known as raltegravir, was the first IN inhibitor drug approved by the United States Food and Drug Administration (US FDA).…”
Section: Research Articlementioning
confidence: 99%